1990
DOI: 10.7883/yoken1952.43.29
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Virus Antibody Among Healthy Blood Donors and Non-A, Non-B Hepatitis Patients in Thailand

Abstract: SUMMARY:With the antigen expressed in yeast from a cDNA clone encoding a non-structural region of newly discovered hepatitic C virus (HCV) genome, the prevalence of HCV antibody in people in Thailand was investigated. Antibody was detected in 2.6% of healthy blood donors and in 2.8% of healthy pregnant women. These prevalence rates were higher than those reported previously from Japan, USA and European countries. Among community-acquired, sporadic cases of acute and chronic non-A, non-B hepatitis, however, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…However, among patients with chronic liver disease but without chronic hepatitis B, HCV infection has been found to be much more prevalent than in the current study [Chen et al, 1990;Kiyosawa et al, 19901. Also, although the numbers were small, none of the seven patients with hepatocellular carcinoma in our study had anti-HCV, which contrasts with 11-70% of patients in other countries [Boonmar et al, 1990;Coursaget et al, 1990;Chang et al, 1992;Farinati et al, 1992;Ramesh et al, 1992;Simonetti et al, 19921. There are several potential explanations for the low level of HCV infection in patients with chronic liver disease in this Peruvian population. First, there may be other factors responsible for the development of chronic liver disease in this population that are independent of HCV or HBV infection.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…However, among patients with chronic liver disease but without chronic hepatitis B, HCV infection has been found to be much more prevalent than in the current study [Chen et al, 1990;Kiyosawa et al, 19901. Also, although the numbers were small, none of the seven patients with hepatocellular carcinoma in our study had anti-HCV, which contrasts with 11-70% of patients in other countries [Boonmar et al, 1990;Coursaget et al, 1990;Chang et al, 1992;Farinati et al, 1992;Ramesh et al, 1992;Simonetti et al, 19921. There are several potential explanations for the low level of HCV infection in patients with chronic liver disease in this Peruvian population. First, there may be other factors responsible for the development of chronic liver disease in this population that are independent of HCV or HBV infection.…”
Section: Discussioncontrasting
confidence: 82%
“…Patients with chronic hepatitis, cirrhosis, and hepatocellular carcinoma have been noted in various studies to have a n increased prevalence of anti-HCV. The frequency of HCV infection in these conditions has varied from population to population and has been higher in patients without chronic hepatitis B [Boonmar et al, 1990;Bruix et al, 1989;Bisceglie et al, 1991;Chang et al, 1992;Chia et al, 1991;Chuang et al, 1992;Colombo et al, 1991;Kew et al, 1990;Lai et al, 1992;Levrero et al, 1991;Poynard et al, 1991;Shimizu et al, 1992;Simonetti et al,…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of past infection with HCV is 0 18 to 2.6% of healthy blood donors in the different countries (5)(6)(7)(8)(9). Furthermore, several reports have shown that HCV infection might be associated with the development of hepatocellular carcinoma (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…At the King Faisal Specialist Hospital and Research Centre, the incidence is 40% [17] and in this edition of the Annals, Fakunle [18] reports 53.7%. Among patients with hepatocellular carcinoma, the incidence varies between 11% and 60.8% [10,19] but in Japan, is up to 94.4% [20]extremely high compared to the 34.5% prevalence of hepatitis B positivity in hepatocellular carcinoma. Of some surprise is that HCV has been found in association in 11% to 29% of patients with chronic hepatitis B, a higher figure occurs with DNA activity [21].…”
mentioning
confidence: 97%
“…Seroprevalence studies using the first generation ELISA test have been conducted on healthy people and patients with variety of chronic liver disease and other problems. Thus, in healthy blood donors, the prevalence of positive hepatitis C (HCV) antibodies generally varies from 0.42% in Germany [8] to 1.4% in New York [9] but 2.6 in Thailand [10] and up to 4.6% in China [11]. In patients with post-transfusion associated'chronic NANB, the incidence is between 60% and 84% [12] and in patients with non-transfusion associated chronic NANB, the incidence is between 58% to 92% [12,13].…”
mentioning
confidence: 99%